2017
DOI: 10.1186/s13062-017-0187-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial tail anchors can target to the mitochondrial outer membrane

Abstract: BackgroundDuring the generation and evolution of the eukaryotic cell, a proteobacterial endosymbiont was re-fashioned into the mitochondrion, an organelle that appears to have been present in the ancestor of all present-day eukaryotes. Mitochondria harbor proteomes derived from coding information located both inside and outside the organelle, and the rate-limiting step toward the formation of eukaryotic cells may have been development of an import apparatus allowing protein entry to mitochondria. Currently, a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…In this study, we have demonstrated that a predicted membrane insertion sequence obtained from a prokaryote can be directed to the peroxisomes of eukaryotic cells. Our findings expand upon earlier studies in which protein sequence derived from prokaryotes could traffic to eukaryotic organelles, such as ER and mitochondria 25,[61][62][63][64][65] . We propose that the ability to direct prokaryotic protein sequences to eukaryotic organelles, even though these regions were not previously selected for targeting prowess in eukaryotes, might have been of general benefit to eukaryotes over evolutionary time.…”
Section: Why Is Protein Targeting To Eukaryotic Organelles So Permisssupporting
confidence: 84%
See 4 more Smart Citations
“…In this study, we have demonstrated that a predicted membrane insertion sequence obtained from a prokaryote can be directed to the peroxisomes of eukaryotic cells. Our findings expand upon earlier studies in which protein sequence derived from prokaryotes could traffic to eukaryotic organelles, such as ER and mitochondria 25,[61][62][63][64][65] . We propose that the ability to direct prokaryotic protein sequences to eukaryotic organelles, even though these regions were not previously selected for targeting prowess in eukaryotes, might have been of general benefit to eukaryotes over evolutionary time.…”
Section: Why Is Protein Targeting To Eukaryotic Organelles So Permisssupporting
confidence: 84%
“…The E. coli YgiM(TA) was detected at peroxisomes, with no microscopic or functional evidence of mitochondrial localization in yeast or in human cells. Conversely, TAs found within two other proteins encoded by the same organism, YqjD and ElaB, targeted to mitochondria and ER, with no evidence of peroxisomal localization 25 [and this study]. Other tail-anchored proteins can target to both mitochondria and peroxisomes.…”
Section: What Features Of Ygim(ta) Allow Targeting To Peroxisomes?mentioning
confidence: 68%
See 3 more Smart Citations